Kebermaknaan hidup dan kesejahteraan psikologis pada perempuan suku Jawa yang menikah muda dan tinggal di Jawa Tengah - Reyna Renata; Arthur Huwae (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
The meaningfulness of life is one of the important factors needed when individuals want to improve their psychological well-being. Similar to the Javanese women who have to accept the conditions of young marriage with various impacts and demands. Therefore, Javanese women who married at a young age need to have meaningfulness in life in order to enhance their psychological health and be able to endure and enjoy their married lives. This research aimed to determine the relationship between the meaningfulness of life and psychological well-being among young married Javanese women. The research method utilized correlational quantitative. A total of 147 Javanese women who married at a young age were included in this research using the snowball sampling technique. The scales used in this research were The Meaning in Life Questionnaire and the Ryff Psychological Well-Being Scale. The results of the hypothesis test with Spearman were 0.197 with sig = 0.000 (p<0.01), which indicates the hypothesis was accepted. The results illustrate that the meaningfulness of life is one of the factors of psychological well-being in Javanese women who married at a young age. This can be interpreted as a connection between changes in psychological well-being and changes in one's perception of the meaningfulness of life.